05/27/2014, 12:23 PM

Well we get exp(x) replaced by exp(f(x)) and ln(x) replaced by f^[-1](ln(x)).

Hence we arrive at f ( f^[-1](a) + f^[-1](b) ) = a + b

( with f at least C^3 )

now differentiate with respect to a :

f ' (f^[-1](a) + f^[-1](b)) / f ' (f^[-1](a)) = 1

substitute X = f(a) , Y = f^[-1](b) :

f ' ( a + Y) = f ' (a)^2

Now rewrite f ' = G and differentiate with respect to Y :

G ' (Y + a) = 0

Hence G is constant and thus f = lineair.

Since f(0) = 0 we conclude f(x) = C x.

thus it only holds for r = 0,1

QED

regards

tommy1729

Hence we arrive at f ( f^[-1](a) + f^[-1](b) ) = a + b

( with f at least C^3 )

now differentiate with respect to a :

f ' (f^[-1](a) + f^[-1](b)) / f ' (f^[-1](a)) = 1

substitute X = f(a) , Y = f^[-1](b) :

f ' ( a + Y) = f ' (a)^2

Now rewrite f ' = G and differentiate with respect to Y :

G ' (Y + a) = 0

Hence G is constant and thus f = lineair.

Since f(0) = 0 we conclude f(x) = C x.

thus it only holds for r = 0,1

QED

regards

tommy1729